Pembinaan Pembentukan Karakter dalam Pencegahan Bullying pada Siswa SDN 129 Panca Karya - Umar Dani; Prapti Octavia Ningsih; Nurkomaria Nurkomaria; Dewi Dewi; Yulia Meilinda (Yayasan Literasi Sains Indonesia, 2026)
Bullying is a problem that is still frequently found in elementary schools and can have a negative impact on students' psychological, social, and academic development. Elementary schools, as the initial phase of character formation, have a strategic role in instilling positive values ​​as an effort to prevent bullying behavior. This community service activity aims to strengthen student character formation through various educational activities as an effort to prevent bullying at SDN 129 Panca Karya. The activity implementation method uses a participatory approach involving students, teachers, and school officials through stages of anti-bullying socialization, character education, positive behavior habits, and student mentoring. The activity was carried out at SDN 129 Panca Karya, Panca Karya Village, Limun District, Sarolangun Regency for approximately 45 days. Evaluation of the activity was carried out through observation, interviews, and documentation to determine the implementation of the program and its impact on student behavior. The results of the activity showed that character building was carried out through the habituation of religious values, discipline, responsibility, social care, empathy, and mutual respect in learning activities and daily school life. The activities implemented have had a positive impact on student behavior, marked by increased empathy, reduced teasing and exclusion of peers, and the creation of more harmonious social interactions. Thus, character development through socialization, education, habituation, and mentoring can be an effective strategy in supporting bullying prevention in elementary school students. The sustainability of the program requires collaboration between schools, teachers, parents, and the surrounding community to create a safe, comfortable, and character-based school culture.